A methodology to evaluate occupational internal exposure to fluorine-18 - Oliveira, C. M.; Dantas, A. L. A.; Dantas, B. M. (Cellular and Molecular Biology, 2009)
The objective of this work is to develop procedures for internal monitoring of 18F to be applied in cases of possible incorporation of fluoride and 18FDG, using in vivo and in vitro methods of measurements. The Na I (Tl) 8”x 4” scintillation detector installed at IRD-Whole Body Counter was calibrated for measurements with a whole body anthropomorphic phantom, simulating homogeneous distribution of 18F in the body. The NaI(Tl) 3”x 3” scintillation detector installed at the IRD-Whole Body Counter was calibrated for in vivo measurements with a brain phantom inserted in an artificial skull, simulating 18FDG incorporation. The HPGe detection system installed at the IRD-Bioassay Laboratory was calibrated for in vitro measurements of urine samples with 1 liter plastic bottles containing a standard liquid source. A methodology for bioassay data interpretation, based on standard ICRP models edited with the software AIDE-version 6, was established. It is concluded that in vivo measurements have sufficient sensitivity for monitoring 18F in the forms of fluoride and 18FDG. The use of both in vitro and in vivo bioassay data can provide useful information for the interpretation of bioassay data in cases of accidental incorporation in order to identify the chemical form of 18F incorporated.